THE FUTURE OF VARIABLE COSTING UNDER A JIT AND AUTOMATED MANUFACTURING - Revrisond Baswir (Faculty of Economics and Business, Universitas Gadjah Mada, 1993)
The emergence of JIT and automated manufacturing have raised aquestion about the relevance of variable costing. Although most accountantsagree with the decrease of important of variable costing, some do not. White somesay that absorption costing would become the only meaningful costing method,others argue that, by a few adjustments, it is possible to keep the variable-costingformat as a useful managerial tool.